English Teaching and Mastering for Learners with Intellectual Disabilities: A Literature Review - Ilham Rizky Infantri; Lintangsari, Alies Poetri (The Center for Disability Studies and Services Brawijaya University, 2022)
The purpose of this research is to find out the challenges and obstacles that arise in teaching through analysis of review papers over the last 10 years with a traditional literature review approach. This study aims at investigating English Teaching and Mastering for Learners with Intellectual Disabilities according to a literature review that the researchers found in a reputable journal. The researcher used traditional literature review. Based on the ten articles analysis, teaching and mastering English for learners with intellectual disabilities have some challenges, obstacles and methods depending on the grade level. Several challenges and obstacles in teaching and mastering have been solved. This study aims to reveal English Teaching and Mastering for Learners with Intellectual Disabilities. Knowing the teaching and mastering process in teaching English for learners with Intellectual Disability is important in order to know what to change from our educational system. Problems inevitably happen in teaching English, especially when teaching learners with disabilities.